"Merciless Indian Savages": Deconstructing Anti-Indigenous Framing. Issue 4 (October 2022) - Mackay, Ried E.; Feagin, Joe
In this article, we identify and develop the specific anti-Indigenous subframe of the long dominant larger white racial frame. Using sociological concepts of systemic racial oppression, we show how the anti-Indigenous subframe co-naturalizes race concepts and specific racist language, embedding a deep and lasting negative framing of Native Americans in the U.S. society. We utilize the Google Ngram Viewer for digitized document identification and retrieval, an important social science tool for finding major historical documents for analysis. Using important documents, we identify a very specific language of Indigenous oppression and examine its central role in anti-Indigenous racial framing, past and present. We demonstrate how powerful and influential political, religious, and scholarly figures and major institutions have developed this racist framing over centuries of systemic Indigenous oppression in the United States. Our analysis adds to the body of social science knowledge by explicating how Indigenous oppression on a systemic level has been perpetuated, rationalized, and legitimated by means of a broad white racial frame and its powerful anti-Indigenous subframe.